Etnoekologi Masyarakat Nelayan Pantai Pancer dan Pantai Lampon Kecamatan Pesanggaran Kabupaten Banyuwangi Serta Pemanfaatannya Sebagai Poster Ilmiah - Della Venda Laudhinez (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Ethnoecology is the study of the close relationship between humans, living spaces, and various activities carried out on earth. This study aims to determine the fishing strategies, fishing gear, and traditions carried out by fisherman at Pancer Beach and Lampon Beach, Pesanggaran District, Banyuwangi Regency. This type of research is an exploratory description with qualitative methods. Data collection was carried out through observation, semi-structured interviews with open-ended questions, and documentation. The results of the study show the strategies used by fisherman at Pancer Beach and Lampon Beach, starting from knowing various weather signs, wind seasons, signs of fish presence, and directions when fishing. The fishing gear used by fisherman at Pancer Beach and Lampon Beach varies greatly depending on the type of fish to be caught. Fishing gear used includes jareng, panceng, mrawe, grenet, octopus bait, squid bait, urang-urangan, and fish aggregating devices (FADs). In addition, fisherman at Pancer Beach and Lampon Beach still consistently carry out the tradition of petik laut as the main tradition directly related to fishing activities. This tradition is seen as a form of gratitude for abundant blessings. The scientific poster validation results had an average percentage of 91.42%, falling within the criteria of very feasible, meaning the new product is ready for use in the field by the community.
FINALISASI oleh Agus 2026 Juni 17
Keywords: Etnoekologi; Nelayan